2020
DOI: 10.3390/nu12082257
|View full text |Cite
|
Sign up to set email alerts
|

Myoprotective Whole Foods, Muscle Health and Sarcopenia: A Systematic Review of Observational and Intervention Studies in Older Adults

Abstract: Decline in skeletal muscle strength and mass (sarcopenia) accelerates with age, leading to adverse health outcomes and poor quality of life. Diet plays a crucial role in muscle ageing being an important element of a healthy lifestyle. However, unlike single nutrients, such as dietary protein, or dietary patterns, such as the Mediterranean diet, the relationship between individual whole foods and muscle health has not been systematically evaluated. We aimed to investigate which whole foods (meat, fish, eggs, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 72 publications
1
26
0
1
Order By: Relevance
“… 4 Reducing dairy, poultry, and eggs to the targets would have smaller sustainability impacts 4 and little health benefit, 51 and some populations may benefit from increasing their currently low intakes of these foods closer to the targets. 29 , 52 , 53 Our findings show that few countries in 2018 met the Eat– Lancet target for reduced total red meat (3·8% of countries, based on a target of ≤98 g/week of unprocessed red meat and processed meat combined [processed meat included processed poultry]), less than half for fish (43·2% of countries ≤196 g/week of seafood), and eggs (33·5% of countries ≤91 g/week), but most for dairy (83·8% of countries ≤250 g/day of milk, cheese, and yoghurt combined).…”
Section: Discussionmentioning
confidence: 99%
“… 4 Reducing dairy, poultry, and eggs to the targets would have smaller sustainability impacts 4 and little health benefit, 51 and some populations may benefit from increasing their currently low intakes of these foods closer to the targets. 29 , 52 , 53 Our findings show that few countries in 2018 met the Eat– Lancet target for reduced total red meat (3·8% of countries, based on a target of ≤98 g/week of unprocessed red meat and processed meat combined [processed meat included processed poultry]), less than half for fish (43·2% of countries ≤196 g/week of seafood), and eggs (33·5% of countries ≤91 g/week), but most for dairy (83·8% of countries ≤250 g/day of milk, cheese, and yoghurt combined).…”
Section: Discussionmentioning
confidence: 99%
“…The pattern we identified was positively associated with fish, soybean products, potatoes, most vegetables, mushrooms, seaweeds and fruits. In a recent review of studies of the relationship between individual whole foods and muscle health, a higher intake of fruits and vegetables was beneficial for muscle function in observational studies [43]. Although there was limited or inconclusive evidence for other whole foods (e.g., fish and soy products) in relation to sarcopenia and muscle-related outcomes [43], a combination of these food groups may contribute to nutrient adequacy for a range of nutrients for sarcopenia and muscle-related outcomes in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review showed a positive association between fruit and vegetables intake (separate and together) and several measures of muscle strength and function, i.e., walking speed, chair rise, Timed Up and Go Test (TUG), Senior Fitness Test, grip strength, and leg extension strength in a population aged over 70 years. These findings have been challenged by the scarce evidence from intervention studies concerning the effect of a diet rich in vegetables on muscle strength and sarcopenia [ 57 ]. The mechanisms through which a diet rich in vegetables may offer myoprotection are not completely understood, it is possible that different constituents in vegetables may have anti-oxidative and anti-inflammatory properties, potentially enhancing muscle function.…”
Section: Discussionmentioning
confidence: 99%